Stability Without Domination: An Analysis of the Financial Performance of PT Siloam Internasional Hospitals Tbk in the Context of Competition Among Publicly Listed Private Hospital Issuers in Indonesia - Yanuar Ramadan; Christin; Christina Wangsa; Fransisca Permana; Sylvia D Tanimulia (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study explores the financial performance of PT Siloam International Hospitals Tbk (SILO) from 2022 to 2024 and compares it with three other publicly listed private hospital operators in Indonesia: PT Mitra Keluarga Karyasehat Tbk (MIKA), PT Medikaloka Hermina Tbk (HEAL), and PT Bundamedik Healthcare System Tbk (BMHS). Employing a longitudinal descriptive approach, the analysis integrates financial ratios (liquidity, solvency, profitability, and asset efficiency), trend evaluations, common size assessments, and growth indices. Findings reveal that while SILO maintains a healthy capital structure and adequate liquidity, it continues to lag behind MIKA and HEAL in terms of profitability and asset utilization. Despite moderate growth in return ratios, SILO’s narrow operating margins and declining asset turnover suggest underutilization of hospital infrastructure and high operating costs. The study underscores the need for operational efficiency, enhanced service monetization, and strategic capital deployment to boost SILO’s competitiveness in the premium healthcare segment. This research contributes to the financial management literature in healthcare and offers practical recommendations for hospital executives, investors, and regulators seeking to strengthen financial sustainability in the private hospital sector.